Retinal Vascular Occlusive Disorders - Risk Factors - Priyanka Agnihotri, Smriti Gupta, Shivcharan Lal Chandravanshi, Sunil Kumar Shrivastava, (International Journal of Innovative Research in Medical Science, 2018)
Aims and Objective - The aim of the present study is to identify risk factors associated with different retinal vascular occlusive diseases (RVOD), such as central retinal artery occlusion (CRAO), hemi-retinal artery occlusion (HRAO), branch retinal artery occlusion (BRAO), cilioretinal artery occlusion (Cilio-RAO), central retinal vein occlusion (CRVO), branch retinal vein occlusion (BRVO), and hemi-retinal vein occlusion (HRVO). Patients and Method - A cross-sectional study on 114 consecutive subjects, aged 24-96 years who have attended at the outpatient department of ophthalmology at Shyam Shah Medical College, Rewa, MP, were included in the study. The Duration of study was January 2016 to December 2017. Only patients with CRAO, BRAO, HRAO, Cilio-RAO, CRVO, BRVO, and HRVO were included in the study. Other retinal vascular disorders such as diabetic vaso-occlusive disease, anterior and posterior ischemic and non-ischemic neuropathy, hypertensive retinopathy, sickle cell retinopathy, retinal telangiectasia, retinopathy of prematurity, were excluded from study. Results - We have included 114 patients, 64 cases (56.14%) males, 50 (43.85%) females, aged 56+/-8 years (range 24-96 years). Bilateral retinal vascular occlusive disorders were seen in only 4 cases (3.5%). Two patients have bilateral CRVO followed by one case of bilateral BRVO and one case of bilateral CRAO. Out of 114 patients, branch retinal vein occlusion was seen in 62 cases (54.38%), followed by central retinal vein occlusion in 36 cases (31.57%), CRAO in 8 cases (7.01%), and hemi- retinal vein occlusion in 4 cases (3.50%). Hypertension was the most common, (40 cases, 35.08%) risk factor identified for retinal vascular occlusive disorders followed by diabetes 24 cases (21.05%), combined diabetes and hypertension in 22 cases (19.29%), and atherosclerosis in 18 cases (15.78%). Conclusions - Retinal vascular occlusive diseases have systemic as well as ocular risk factors. Understanding of these risk factors is essential for proper treatment of RVOD. Timely identification of risk factors for RVOD may helpful in decreasing ocular and systemic morbidity in these patients.